Structural, Vibrational and Electronic Properties with Pharmacokinetics, Drug likeness, and Molecular Docking of Furandimethanol - Bhatt, Madhab Raj; Dhami, Govind Bahadur; Joshi, Shiv Raj (Api Journal of Science, 2025)
In this study, geometrical parameters, electronic and vibrational properties of furandimethanol (BHMF) have been analyzed by using density functional theory (DFT) at B3LYP/6-31g level. Forty-five normal modes of vibration were obtained and analyzed with their potential energy contributions. The calculated Raman and IR spectra were plotted using scaled wavenumbers. Molecular electrostatic potential surface (MESP), ultraviolet visible (UV-Vis) spectra and Mulliken charges were mapped to understand electronic properties. Swiss ADME web tool was used for prediction of physicochemical, pharmacokinetics, drug-likeness and medicinal properties of titled molecule. Molecular docking studies against 1S5B (2.13 Å resolution), a mutant cholera holotoxin from Vibrio cholerae, were performed using Auto dock tools like BIOVIA Discovery Studio, PyMOL, Python and Open Babel. The molecular docking study indicates that the furandimethanol is moderate inhibitor of 1S5B.